(untitled) (Biological Sciences - PJSIR, 2001)
5,7-Dihydroxy-8-C-prenyltlavanone (VII, glabranin) Mitscher et a11983) isolated from the roots and stems of Glycyrriza lepidota has been synthesized by following unambigous route. All the new products have been characterized on the basis of spectral data.